A Theory of Innovation Valuation - Jiang, Jun (International Journal of Development Administration Research, 2025)
Aiming at an effective assessment of the intrinsic value of an innovative firm, the study is designed to explore the factoring of riskiness from innovation activities theoretically into the valuation of corporations. With the success of risk incorporated into corporate value, the market is going to allocate the capital optimally into innovative firm therefore beneficial to economic sustainability and wealth maximization. The study proposes a conceptual framework to quantify the risk effects into free case flows that, in turn, determine the corporate value. It is rationally argued by the study that the key nature of innovation is the risk taken by firms. The riskiness taken by the firm will impact not only the operating cash flows but also the required rate of return. With innovation, riskiness is factored into the value of operating cash flows; the corporate intrinsic value integrates the innovation riskiness. Nevertheless, the market does not simultaneously discover the innovation value as part of the share value at the same time as the authentic intrinsic value does. The results establish the linkage between the riskiness of innovation and corporate valuation and recommend an effective methodology for further exploration of intrinsic value. In addition, the study proposes the gap between the recognition of innovation value by intrinsic and market value.